Fault-controlled development of shallow hydrothermal systems: Structural and mineralogical insights from the Southern Andes. (March 2017) - Roquer, Tomás; Arancibia, Gloria; Rowland, Julie; Iturrieta, Pablo; Morata, Diego; Cembrano, José
Highlights: We combine field, mineralogical data and mechanical models. We study the interplay between mineral precipitation and brittle deformation. We estimate hydromechanical conditions for different modes of failure. We identify structurally ideal places for concentrated hydrothermal activity. Abstract: Paleofluid-transporting systems can be recognized as meshes of fracture-filled veins in eroded zones of extinct hydrothermal systems. Here we combined meso-microstructural analysis of 107 fractures and mechanical modeling from two exhumed exposures of the faults governing regional tectonics of the Southern Andes: the Liquiñe-Ofqui Fault System (LOFS) and the Andean Transverse Faults (ATF). The ATF specific segment shows two tectonic solutions that can be modeled as Andersonian and non-Andersonian tectonic regimes: (1) shear (mode II/III) failure occurs at differential stresses > 28 MPa and fluid pressures < 40–80% lithostatic in the Andersonian regime; and (2) sporadic hybrid extensional + shear (modes I + II/III) failure occurs at differential stresses < 20 MPa and anomalously high fluid pressures > 85–98% lithostatic in the non-Andersonian regime. Additionally, the LOFS exposure cyclically fails in extension (mode I) or extension + shear (modes I + II/III) in the Andersonian regime, at differential stresses < 28 MPa and fluid pressures > 40–80% lithostatic. In areas of spatial interaction between ATF and LOFS, these conditions might favor: (1) the storage of overpressured fluids in hydrothermal systems associated with the ATF faults, and (2) continuous fluid flow through vertical conduits in the LOFS faults. These observations suggest that such intersections are highly probable places for concentrated hydrothermal activity, which must be taken into consideration for further geothermal exploration.